2008
DOI: 10.1103/physrevlett.100.125502
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-Scale Visualization of Antisite Defects inLiFePO4

Abstract: We visualize the antisite exchange defects in LiFePO4 crystals with an ordered olivine structure by using annular dark-field scanning transmission electron microscopy (STEM). A recognizable bright contrast is observed in some of the Li columns of STEM images in a sample annealed at a lower temperature, which directly demonstrates the disordered occupations by Fe atoms. Furthermore, such exchange defects appear to be locally aggregated rather than homogeneously dispersed in the lattice, although their overall c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
103
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 175 publications
(114 citation statements)
references
References 17 publications
10
103
0
1
Order By: Relevance
“…This appears not to be the case, however when cation site exchange is found in samples prepared by low temperature synthesis [7][8][9] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This appears not to be the case, however when cation site exchange is found in samples prepared by low temperature synthesis [7][8][9] .…”
Section: Resultsmentioning
confidence: 99%
“…In the specific case of LiFePO 4 , several diffraction studies on materials prepared *Manuscript Click here to view linked References by low temperature routes have shown a small amount of Li, Fe cation exchange in samples prepared hydrothermally and using wet chemistry 7,8 . A small concentration of Fe on Li sites was visualised in LiFePO 4 crystals using dark field scanning transmission electron microscopy, STEM 9 . Above ~180 °C, a fully ordered structure occurred in samples that were prepared hydrothermally as well as by direct solid state reaction.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the reported experimental data showing the presence of various native defects in LiFePO 4 samples. [12][13][14][15][16][17][18][19] We note that there are several limitations inherent in our calculations. The first set of limitations comes from standard methodological uncertainties contained in the calculated formation enthalpies and phase diagrams as discussed in Ref.…”
Section: Tailoring Defect Concentrationsmentioning
confidence: 99%
“…Experimental reports on the defects have, however, painted different pictures. Some authors reported evidence of some iron and lithium atoms exchanging sites and forming the antisite pair Fe Li -Li Fe , 17,19 while others determined that Fe Li is formed in association with lithium vacancies (V Li ). 15,18 These conflicting reports suggest that the results may be sensitive to the actual synthesis conditions, and indicate that a better understanding of the formation of native defects in LiFePO 4 is needed in order to produce samples with controlled defect concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation